Factors influencing diversity of farmers' varieties of sweet potato in Uganda: implications for conservation. - Zawedde, Barbara M.; Harris, Craig; Alajo, Agnes; Hancock, Jim; Grumet, Rebecca (The New York Botanical Garden Press, Bronx, NY 10458-5126 U.S.A., 2014)
There is increasing concern that agricultural intensification is causing loss of crop biodiversity due to displacement of traditional farmers’ varieties by a small number of improved cultivars. Using ethnobotanical surveys, we assessed the implication of adoption of new sweet potato (Ipomoea batatas) cultivars on the maintenance of farmers’ varieties in Uganda. Other factors influencing varietal diversity were also assessed. A total of 102 farmer households distributed in the top three sweet potato production agro-ecological zones were interviewed. With the exception of released cultivars, very few varieties appeared in more than one region. The majority of the respondents indicated that they continue to plant some of the existing varieties when they adopt new cultivars. Loss of planting materials due to drought was a major constraint to maintaining varietal diversity for this vegetatively propagated crop. Limited land and lack of access to best management practices were also key constraints to maintenance of farmers’ varieties. The primary criteria for adopting new cultivars were higher yield, taste, and duration to maturity. Yield stability, tolerance to native biotic and abiotic stresses, and good taste were important for maintenance of currently grown varieties. Overall, criteria for variety selection varied with household characteristics including farmer age and gender, uses of the crop, micro-climatic conditions in the farmers’ fields, and level of access to agricultural extension. The observed heterogeneity in selection criteria, influence of social ties, and the role of environment in varietal maintenance have important implications for establishing breeding priorities and preservation of crop diversity.
Keywords: Crop biodiversity, cultivar adoption, farmers’ varieties, Ipomoea batatas, land races, ethnobotany.